Quality and antioxidant properties of extruded breakfast cereal containing encapsulated turmeric extract - Natcha Laokuldilok (2018)
© 2017, Chiang Mai University. All rights reserved. Encapsulated turmeric extract (ETE) using a binary blend of wall materials, comprising brown rice flour and beta-cyclodextrin, was used for the addition of 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7% and 8% of the same for making extruded breakfast cereals. The physical quality, total phenolic content (TPC), curcuminoid content, and antioxidant activities were analyzed. The hardness, crispness, color for L* and b* values, TPC, and curcuminoid content of the extruded products were found to be increased with the addition of ETE. The moisture content, water activity, expansion ratio, and density of the extruded products were observed to be decreased with the addition of ETE. The extruded cereals containing ETE showed good antioxidant activities, as well,when tested using the DPPH and the ABTS scavenging methods. A 5% addition of ETE showed acceptable sensory scores. Therefore, it can be concluded that breakfast cereal containing ETE can be developed as functional food for promoting health.